Imposter phenomenon and basic psychological needs predict self-evaluations of knowledge and ability relative to others - Biblekaj, Viktoria; Kahlbaugh, Patricia (International Journal of Personality Psychology, 2026)
Imposter Phenomenon (IP) is a set of psychological experiences characterized by self-doubt, attributing success to external causes, and a constant fear of being perceived as a phony (Clance & Imes, 1978), which may be suggestive of dissatisfaction with basic psychological needs of competence, autonomy, and relatedness. Amazon Mechanical Turk (MTurk) workers (N = 325, 61% men, 39% women) ranked their self-identified knowledge and abilities relative to others, completed the Clance Imposter Phenomenon Scale (CIPS) assessing IP, and the Balanced Measure of Psychological Needs (BMPN) assessing competence, autonomy, and relatedness. We hypothesized that IP and dissatisfaction in basic psychological needs would predict underestimation of knowledge and abilities relative to those of other people. However, we found imposter phenomenon and basic psychological needs predicted positive self-evaluations. Inflated self-evaluations may be strategically used to defend against IP feelings and against a sense of “ill-being” associated with thwarted psychological needs. Thus, a positive, confident presentation may be compensatory or defensive in nature. Future research could explore specific defense mechanisms that may mediate this positive self-evaluation of knowledge and ability relative to others as well as the role of styles of perfectionism.
Keywords: Basic needs; Feeling; Need theory; Phenomenon; Scale (ratio); Set (abstract data type); dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Zenodo (CERN European Organization for Nuclear Research), 2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (2026)
(1) Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g., gamete interactions), which are likely affected by temperature. (2) Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. (3) We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus. Under typical thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favor preferred, dominant males over sneaker males. (4) We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. (5) Our results highlight that considering the thermal sensitivity of female-male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction, and sexual selection.
Keywords: Climate change; Gamete; Mate choice; Mating; Mating system; Operational sex ratio; Sexual selection; Sperm; dept.psy

Role of an Intermediary Organization and State Government Partnership to Advance Practice and Policy in Children’s Behavioral Health - Lang, Jason; Randall, Kellie; Kelly, A.; Bracey, Jeana; Bridges-Hightower, Jenny; Newkirk, Katie; Lu, Jack; Gregory, Francis; Duran, Tracy; Geib, Catherine; Bozak, Stephanie; Mackey, Jocelyn; et al. (Prevention Science, 2026)
Keywords: Behavioral health; Bridge (graph theory); Diversity (politics); General partnership; Government (linguistics); Intermediary organization; Partnership; Plan (archaeology); Policy; Public policy; Research; State (computer science); System development; Workforce; Workforce development; dept.psy

Actigraphy-based sleep outcomes in substance use disorders: A systematic review and meta-analysis - Naveda, Alisson; Oliva, Henrique; Pulido-Saavedra, Alejandra; Ghadimi, Delaram; Moore, James; Morgan, Peter; Potenza, Marc; Angarita, Gustavo (Sleep Medicine Reviews, 2026)
Keywords: MEDLINE; Polysomnography; Sleep (system call); Substance use; Systematic review; dept.psy

Thinking differently: neurodivergent traits and responses to thought experiments in philosophers and the general population - McKee, Paul; Boulhadi, Khaoula; Weymouth, Helena; Nadelhoffer, Thomas (Philosophical Psychology, 2026)
Philosophers have long speculated that individual differences in temperament influence philosophical thinking, yet empirical research has rarely explored the role of neurodivergent traits in this domain. In this large online study (N = 1,254), we investigated whether participants with training in philosophy differ from the general population when it comes to six psychological traits–autism, ADHD, aphantasia, anendophasia, anauralia, and representational manipulation–and also whether these traits correlate with responses to two widely studied philosophical thought experiments: the “trolley problem” and the “rollback deterministic universe.” Compared to the general population, participants with training in philosophy had higher scores on measures of ADHD, internal verbalization, and representational manipulation, but lower scores on measures of visual imagery. These cognitive traits were also correlated with participants’ moral and metaphysical judgments (independent of their level of philosophical training)–e.g. participants who scored higher in visualization were less likely to judge that hitting the switch in the trolley problem is permissible but not obligatory, and also less likely to attribute free will and moral responsibility to agents in the rollback universe. Finally, we employed machine learning to develop predictive models that classify a randomly selected participant as either a philosopher or a non-philosopher. Models trained solely on responses to measures for neurodivergent traits achieved better performance than models trained solely on responses to philosophical thought experiments. This suggests that stable, trait-level neurodivergent characteristics may be more diagnostic of philosophical interest, aptitude, or training than judgments philosophers make on domain-relevant problems. © 2026 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Neurodiversity; dept.psy; experimental philosophy; free will beliefs; general population; moral judgment; philosophers

Investigating the analytical robustness of the social and behavioural sciences - Aczel, Balazs; Szaszi, Barnabas; Clelland, Harry T.; Kovacs, Marton; Holzmeister, Felix; van Ravenzwaaij, Don; Schulz-Kümpel, Hannah; Hoffmann, Sabine; Nilsonne, Gustav; Kosa, Livia; Torma, Zoltan A.; Abdelfatah, Yousuf; et al. (Nature, 2026)
The same dataset can be analysed in different justifiable ways to answer the same research question, potentially challenging the robustness of empirical science1-3. In this crowd initiative, we investigated the degree to which research findings in the social and behavioural sciences are contingent on analysts' choices. We examined a stratified random sample of 100 studies published between 2009 and 2018, in which, for one claim per study, at least five reanalysts independently reanalysed the original data. The statistical appropriateness of the reanalyses was assessed in peer evaluations, and the robustness indicators were inspected along a range of research characteristics and study designs. We found that 34% of the independent reanalyses yielded the same result (within a tolerance region of ±0.05 Cohen's d) as the original report; with a four times broader tolerance region, this indicator increased to 57%. Of the reanalyses conducted, 74% reached the same conclusion as the original investigation, 24% yielded no effects or inconclusive results and 2% reported the opposite effect. This exploratory study indicates that the common single-path analyses in social and behavioural research should not be simply assumed to be robust to alternative analyses4. Therefore, we recommend the development and use of practices to explore and communicate this neglected source of uncertainty. © 2026. The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: Behavioural sciences; Empirical research; Exploratory research; Robustness (evolution); Sample size determination; Statistical analysis; dept.psy

General trait and workplace fear of missing out (FoMO) and the neurodiverse mind: Exploring autism, ADHD, and internal representation profiles - McKee, Paul; Boulhadi, Khaoula; Nadelhoffer, Thomas (Personality and Individual Differences, 2026)
Keywords: Mental representation; Psychometrics; Representation (politics); Social perception; Trait; dept.psy

Warm waters undermine cryptic female choice - Kustra, Matthew; Alissa, Louise; Rogers, Michaela; Molinari, M.; Stiver, Kelly; Marsh‐Rollo, Susan; Hellmann, Jennifer; Alonzo, Suzanne (Functional Ecology, 2026)
Abstract Understanding the thermal sensitivity of reproductive interactions is crucial given global warming. Previous studies have almost exclusively focused on interactions before mating, even though important interactions between the sexes also occur after mating (e.g. gamete interactions), which are likely also affected by temperature. Thus, it remains unknown how temperature affects the influence of female reproductive fluid on sperm performance, thereby altering female control over fertilization (cryptic female choice). This gap limits our understanding of how sexual selection changes with seasonal temperature fluctuations and temperatures outside the range of historical norms. We tested how temperatures relevant to current conditions and climate change projections influence the mechanisms underlying cryptic female choice in a marine fish, Symphodus ocellatus . Under typical, cooler thermal conditions, female reproductive fluid enhances sperm velocity and biases fertilization dynamics to favour preferred, dominant males over sneaker males. We find that warmer temperatures decrease female influence on sperm velocity, especially for dominant males. This results in dominant males having slower sperm than sneaker males at warmer temperatures, reducing the expected paternity of preferred, dominant males. Our results highlight that considering the thermal sensitivity of female–male interactions that occur after mating will be essential for understanding how seasonal variation and climate change can influence fertility, reproduction and sexual selection. Read the free Plain Language Summary for this article on the Journal blog.
Keywords: Gamete; Mating; Mating system; Reproduction; Reproductive success; Sexual selection; Sperm; Sperm competition; alternative reproductive tactics; climate change; dept.psy; mating systems; ovarian fluid; sexual selection; sperm competition; thermal ecology

Actigraphy-based sleep outcomes in substance use disorders: A protocol for a systematic review and meta-analysis - Naveda, Alisson; Oliva, Henrique; Ghadimi, Delaram; Angarita, Gustavo (PLoS ONE, 2026)
INTRODUCTION: Individuals with substance use disorders (SUDs) are at increased risk for sleep disturbances, creating a bidirectional relationship that may heighten relapse risk. While polysomnography is the gold standard for measuring sleep, many studies have used actigraphy, a noninvasive, wrist-worn device that estimates rest-activity patterns and sleep-wake characteristics. Despite its utility, the use of actigraphy in populations with SUDs remains limited, and findings vary across substances and methodologies. This protocol outlines a systematic review and meta-analysis aiming to synthesize evidence on actigraphy-derived sleep outcomes across various substances. METHOD AND ANALYSIS: We will include peer-reviewed observational or interventional studies involving individuals aged 18 or older with a diagnosis of substance use (e.g., alcohol, benzodiazepines, cannabis, cocaine, opioids, methamphetamine, or nicotine) who use actigraphy to assess sleep compared to matched controls. Studies will be excluded during screening if they do not use actigraphy, do not include populations with SUDs, or focus on participants younger than 18. There will be no restrictions on location, setting, or language. Databases to be searched include PubMed, Scopus, Web of Science, ProQuest, ClinicalTrials.gov, CINAHL, PsycINFO, and Embase. Titles and abstracts will be screened in the first phase, followed by full-text screening using eligibility criteria. At least two independent reviewers will assess risk of bias using the Risk Of Bias In Non-randomized Studies of Exposures (ROBINS-E) tool. A synthesis will summarize key findings, including study characteristics, population differences, and methodological variations. DISCUSSION: This review will offer a clear and comprehensive assessment of the current literature on actigraphy to examine sleep in SUD and to inform future research to study sleep and its implications in SUD populations. PROTOCOL REGISTRATION NUMBER: International Prospective Register for Systematic Reviews (PROSPERO) number CRD420251072028.
Keywords: MEDLINE; Prospective cohort study; Protocol (science); Substance use; Systematic review; dept.psy